Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Melalui Keterikatan Karyawan - Febriani, Fika Aurelia; Ramli, Abdul Haeba (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Employees are the organization's most important asset and play a strategic role in the organization as constituents and managers of its activities to achieve company goals. Employee performance is the result of work performed by an individual in carrying out a given task. With high employee performance it is hoped that organizational goals can be achieved. Many factors such as motivation are important and work environment that can affect employee performance. The purpose of this study is to prove that there is a relationship between all variables in non-academic staff at a university located in West Jakarta. This study uses a structural equation model (SEM) involving 120 respondents who are non-academic staff employees at the University located in West Jakarta. Analysis of data processing in this study used Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Some of the findings in this study are that Organizational Culture affects Employee Engagement. Meanwhile, employee engagement cannot improve employee performance. Furthermore, organizational culture has a positive influence on employee performance. Conversely, employee engagement cannot mediate organizational culture and employee performance. Keywords : Organizational Culture, Employee Engagement, Employee Performance.